Biomechanical Role of the Superior Capsule in a Rotator Cuff Sectioned and Repaired State: A Sequential Sectioning Study. Issue 6 (May 2022) - DeFroda, Steven F.; Perry, Allison K.; Mehta, Nabil; Muriuki, Muturi G.; McCormick, Johnathon R.; Havey, Robert M.; Clapp, Ian M.; Garrigues, Grant E.; Verma, Nikhil N.
Background: Individual contributions of the rotator cuff (RC) and superior capsule (SC) to prevent superior translation of the humerus are not well understood. Purpose: To evaluate the relative contributions of the SC and RC to normal and pathologic shoulder biomechanics by determining their independent effects on superior humeral translation. Study Design: Controlled laboratory study. Methods: Twelve cadaveric shoulders were tested at 0º, 45º, and 90º of abduction under 5 conditions: intact RC/SC, RC sectioned first, SC sectioned first, both structures sectioned, and RC repair. Matched pairs were randomly assigned to the second or third testing condition (RC or SC sectioned first). Specimens were tested under 2 static conditions (40-N deltoid load [balanced load], 80-N deltoid load [superiorly directed load]) and 1 dynamic condition during active abduction. A mixed-design 2-way repeated-measures analysis of variance with Bonferroni adjustments was performed to compare testing conditions. Paired t tests were used to compare specimens in the intact state versus the repaired state. Significance was set at P < .05. Results: During balanced deltoid loading at 0° and 45º, there was significantly greater humeral translation when both structures were sectioned as compared with the intact state and with both isolated sectioned states ( P < .05 for all). No significant differences were observed between or within groups at 90º of abduction. These effects remained consistent with superiorly directed loading. Dynamic testing of both groups showed a significant increase in superior translation for specimens in which the RC was deficient versus the intact state ( P = .027), with no difference when the SC was sectioned. The RC repair state returned translation to values similar to the intact state at all abduction angles and loading conditions ( P > .05). Conclusion: In this cadaveric study, the SC and RC played an important role in preventing superior humeral translation; however, dynamic testing suggested preferential contribution of the RC. RC repair was effective in preventing superior humeral translation, even with a sectioned SC at the level of the glenohumeral joint. Clinical Relevance: RC repair was effective in preventing superior humeral translation, even in the presence of a sectioned SC at the level of the glenohumeral joint in this cadaveric model. Our data lay the groundwork for future studies investigating the clinical effect of RC repair in an SC sectioned state.